Factors affecting the usability of an assistive soft robotic glove after stroke or multiple sclerosis - Susanne Palmcrantz; Jeanette Plantin; Jörgen Borg
Objective: To explore the usability and effects of an assistive soft robotic glove in the home setting after stroke or multiple sclerosis. Design: A mixed methods design. Methods: Participants with stroke (n  =  10) or multiple sclerosis (n  =  10) were clinically assessed, and instructed to use the glove in activities of daily living for 6 weeks. They reported their experience of using the glove via weekly telephone interviews and one semi-structured interview. Results: The soft robotic glove was used by participants in a wide variety of activities of daily living. Perceived beneficial effects while using the glove were a sustained and a strong grip. Disadvantages of using the glove were a lack of assistance in hand opening function and the glove not being usable for fine hand use. The glove was found to be useful by two-thirds of participants who completed the study, mainly by participants with moderate limitations in hand activity and an overall level of functioning that allowed participation in everyday life activities. Conclusion: This study identified a subgroup of participants, who found the glove useful in activities requiring a strong and prolonged grip but not fine hand use, and highlights aspects for consideration in the further development of soft hand robotics for sustained use in a larger population living with a central nervous system lesion.